0374 Exposure-Response Estimates for Diesel Engine Exhaust and Lung Cancer Mortality Based on Data from Three Occupational Cohorts. (23rd June 2014) - Vermeulen, Roel; Silverman, Debra; Garshick, Eric; Vlaanderen, Jelle; Portengen, Lützen; Steenland, Kyle
Abstract : Objectives: To derive a meta-exposure-response curve (ERC) for DEE and lung cancer mortality and estimate lifetime excess risks (ELRs) of lung cancer mortality based on assumed occupational and environmental exposure scenarios. Method: We conducted a meta-regression of lung cancer mortality and cumulative exposure to elemental carbon (EC), a proxy measure of DEE, based on relative risk (RR) estimates reported by three large occupational cohort studies. Based on the derived risk function, we calculated ELRs for several lifetime occupational and environmental exposure scenarios, and also calculated the fractions of annual lung cancer deaths attributable to DEE. Results: We estimated a lnRR of 0.00098 (95% CI: 0.00055, 0.0014) for lung cancer mortality with each 1-μg/m 3-year increase in cumulative EC. Estimated numbers of excess lung cancer deaths through age 80 for lifetime occupational exposures of 1, 10, and 25 μg/m 3 EC were 17, 200, and 689 per 10 000, respectively. For lifetime environmental exposure to 0.8 μg/m 3 EC, we estimated 21 excess lung cancer deaths per 10 000. Based on broad assumptions regarding past exposures we estimate that approximately 6% of annual lung cancer deaths may be due to DEE exposure. Conclusions: Combined data from three US occupational cohort studies suggest that DEE at levels common in the workplace and in outdoor air appear to pose substantial excess lifetime risks of lung cancer, above usually acceptable limits in the US and Europe, which are generally set at 1/1000 and 1/100 000 based on lifetime exposure for the occupational and general population, respectively.